Financial management to improve competitiveness in Indonesian fintech peer-to-peer lending companies - Dachlan, Rudy Syafariansyah; Wahyuti, Sri; Yulidar Abbas, Muhammad Astri; Rohmah, Siti (Jurnal Mantik, 2025)
The rapid growth of Indonesia’s fintech industry, especially in peer-to-peer (P2P) lending, presents both opportunities and financial risks. This study aims to examine and compare the financial management strategies of two major Indonesian fintech companies—Easycash and Findaya—by analyzing their profitability, liquidity, solvency, and operational efficiency. Using a descriptive comparative design and secondary data from audited financial reports covering the period from 2019 to 2023, the study calculates key financial ratios, including ROA, ROE, Current Ratio, DER, and Efficiency Ratio. Results show that Easycash adopted a high-leverage growth model, experiencing a significant decline in profitability (ROA: 58.7% to 2.6%) and an increase in financial risk (DER reached 2.20). In contrast, Findaya followed a conservative financial strategy, improving performance with increased ROA (-53.8% to 16.0%), higher liquidity (CR: 4.15), and lower debt (DER: 0.32). These contrasting approaches provide insight into risk tolerance, strategy execution, and resilience. The study contributes by offering firm-level evidence on how financial management impacts competitiveness in Indonesia’s fintech sector and serves as a model for evaluating financial strategies in similar emerging markets.